The development of Barcode Inventory Management System for Kerepek Zainab Enterprise / Quraisha Mustapha Kamal - Mustapha Kamal, Quraisha (2017)
Kerepek Zainab Enterprise was established by Zainab binti Abdul Hamid in 24th of October 1998. It is located at Batu 8 Meru, Klang, Selangor. It consists of five staff. It is a private company and the products are processed at her house. The Kerepek Zainab Enterprise is having problem in managing their information of business processes, especially the inventories. Furthermore, the owner of the company wants a system that can minimize the problems that they encounter and that lead to the development of a new system. The aim of this project is to provide an inventory management system using barcode for Kerepek Zainab Enterprise that will systematically enhance the business process. The name of the new system is Barcode Inventory Management System. The methodology that is used to complete the project is by using System Development Life Cycle (SDLC). The development covered three of the methodology phases, which are the Requirement Identification, Design, and Implementation. The requirements of the project are gathered by conducting interviews and observation. The requirement that are gathered will enter the Analyze phase and this phase has used CRUD technique to identify the use case. The deliverables in the first phase of SDLC methodology are recorded in the Software Requirements Specification (SRS). The system design and structures were developed using UML modelling technique and documented in Software Design Document (SDD). An extension of this project is possible in future in order to enhance the performance of the system.